2017
DOI: 10.1177/0256090917703754
|View full text |Cite
|
Sign up to set email alerts
|

Healing a Broken Spirit: Role of Servant Leadership

Abstract: Executive SummaryA number of empirical studies have suggested that servant leadership can enhance the well-being/emotional health of its followers by creating a positive work climate ( Black, 2010 ; Jaramillo et al., 2009 a; Neubert et al., 2008 ). The followers’ sense of well-being, in turn, has been found to be related to greater organizational commitment ( Cerit, 2010 ; Hale & Fields, 2007 ; Hamilton & Bean, 2005 ; Han, Kakabadse, & Kakabadse, 2010; Pekerti & Sendjaya, 2010 ). Greater the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 74 publications
3
55
0
Order By: Relevance
“…The results of the study were overwhelmingly positive towards a servant leadership philosophy practiced within an SWM firm. The literature strongly suggested firms that practice servant leadership adds significant value to their relations with employees (Barbuto & Wheeler, 2006;Franscoise, 2016;Jit, Sharma, & Kawatra, 2017;Guitierrez-Wirsching et al, 2015;Mertel & Brill, 2015), and the interview participants confirmed the earlier findings of the literature re view. All of the participants viewed servant leadership as having a positive impact on their continued employment, identifying many of the aspects outlined in the literature review such as community building, listening, and growth.…”
Section: Applications To Professional Practicesupporting
confidence: 75%
“…The results of the study were overwhelmingly positive towards a servant leadership philosophy practiced within an SWM firm. The literature strongly suggested firms that practice servant leadership adds significant value to their relations with employees (Barbuto & Wheeler, 2006;Franscoise, 2016;Jit, Sharma, & Kawatra, 2017;Guitierrez-Wirsching et al, 2015;Mertel & Brill, 2015), and the interview participants confirmed the earlier findings of the literature re view. All of the participants viewed servant leadership as having a positive impact on their continued employment, identifying many of the aspects outlined in the literature review such as community building, listening, and growth.…”
Section: Applications To Professional Practicesupporting
confidence: 75%
“…However, some researchers criticize SL for being an unrealistic approach (Johnson, 2001) and others for it being a weak, naïve and passive approach (Bowie, 2000). Nevertheless, despite all the criticism, SL has gained popularity and recognition in recent years as a valid organizational leadership style, especially in educational organizations (Al-Asadi et al, 2019;Barnes, 2015;Gary, 2017;Jit et al, 2017;Laub, 1999;Adoramadan et al, 2020;Russell, 2001).…”
Section: Servant Leadershipmentioning
confidence: 99%
“…Characteristics of servant leaders, argues Fahlberg and Toomey (2016), are witnessed in some of the best nursing leaders who speak up, volunteer, and advocate-all of which bring nurses to a place where we can be of value. This is supported by Jit et al (2017) who argue that servant leaders demonstrate compassion and altruistic calling, traits which help to build the foundation of a strong workforce and imbue a sense of 'cohesiveness, collaboration and sustainable relationships'.…”
Section: Nurses As Servant Leadersmentioning
confidence: 97%